Psychological characteristics of athletes in regional training center - Prasetiyo, Rahayu; Bayu, Wahyu Indra; Darisman, Eka Kurnia (Journal Sport Area, 2022)
High achievment in sports requires behavior with certain qualities. Likewise, with successful athletes, they have superior qualities not only in terms of physical but also mentality. This study aims at examining psychological characteristic because it’s one of the important factors possessed by athletes, and can influence them in. The sample used in this study are 198 East Java athletes who participates in the training center from 21 sports. The instrument used for psychological characteristics in this study is the SKPA (Scale of Psychological Characteristics for Athletes) with a factor loading value > 0.5, so that each item is valid in measuring it’s dimensions, and it’s known that the conbrach’s alpha value for each dimension is 0.7. Of the eight psychological characteristics, the highest mean value for hard work is 16.31. And the lowest mean values for opennes is 12.02. Eight psychological characteristics indicate a good category, which means that the psycology of the East Java regional training center athletes are in good condition.